Oxidative Stress as “Mother” of Many Human Diseases at Strong Clinical Impact - Cacciapuoti, Federico (Journal of Cardiovascular Medicine and Cardiology, 2016)
Oxidative stress, characterized by the production in excess of free radicals, is the main aspect of all living systems which use oxygen to convert biochemical energy coming from nutrients into adenosine triphosphate. In turn free radicals, also called reactive oxygen species , induce oxidative damage to some cellular macromolecules, as lipids, proteins, and DNA .Increased reactive oxygen species serum concentration has been implicated in the pathogenesis of some, common human diseases, included both healthy and diseased ageing. The most frequent pathologies involved are: atherosclerosis, cancer, Alzheimer's and Parkinson's Diseases and chronic obstructive pulmonary disease. Together with these, other, less frequent diseases can be interested, as chronic fatigue syndrome, lateral amyotrophic sclerosis and skin diseases. Therefore oxidative stress, that is an imbalance of an essential biochemical reaction physiologically happening in the human body, can be considered as one of the sources of the most common human pathologies and of the aging process.